Data supporting phylogenetic reconstructions of the Neotropical clade Gymnotiformes - Tagliacollo, Victor A. [UNESP]; Bernt, Maxwell J.; Craig, Jack M.; Oliveira, Claudio [UNESP]; Albert, James S. (Elsevier, 2016)
Data is presented in support of model-based total evidence (MBTE) phylogenetic reconstructions of the Neotropical clade of Gymnotiformes Model-based total evidence phylogeny of Neotropical electric knifefishes (Teleostei, Gymnotiformes) (Tagliacollo et al., 2016) [1]). The MBTE phylogenies were inferred using a comprehensive dataset comprised of six genes (5277 bp) and 223 morphological characters for an ingroup taxon sample of 120 of 218 valid species and 33 of the 34 extant genera. The data in this article include primer sequences for gene amplification and sequencing, voucher information and GenBank accession numbers, descriptions of morphological characters, morphological synapomorphies for the recognized clades of Gymnotiformes, a supermatrix comprised of concatenated molecular and morphological data, and computer scripts to replicate MBTE inferences. We also included here Maximum-likelihood and Bayesian topologies, which support two main gymnotiform clades: Gymnotidae and Sternopygoidei, the latter comprised of Rhamphichthyoidea (Rhamphichthyidae+Hypopomidae) and Sinusoidea (Sternopygidae+Apteronotidae).